1994
DOI: 10.1159/000126788
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-Pituitary-Adrenocortical Axis Changes in the Rat after Long-Term Treatment with the Reversible Monoamine Oxidase-A Inhibitor Moclobemide

Abstract: The effects of the reversible monoamine oxidaseA (MAOA) inhibitor moclobemide on the rat hypothalamic-pituitary-adrenocortical (HPA) axis were studied. The time-course experiments showed that moclobemide, given via the drinking water (4.5 mg/kg/day), produces significant decreases (p < 0.05) in adrenal weight after 5 (–23%) and 7 weeks (–16%) of treatment. It was found that long-term moclobemide treatment had neuroanatomically distinct effects on corticosteroid receptor expression. Hippoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
69
0
2

Year Published

1995
1995
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(79 citation statements)
references
References 29 publications
(34 reference statements)
8
69
0
2
Order By: Relevance
“…In the light of the inhibitory effect of MRs on HPA activity which is reflected by studies employing MR antagonists in rats (Spencer et al 1998) and humans (Dodt et al 1993;Young et al 1998) or MR antisense in rats , the observed upregulation of MR capacity seems to be a first step necessary for the inhibition of hypothalamic CRH neurons. This effect on MR is followed by increased GR capacity (Brady et al 1991;Seckl and Fink 1992;Reul et al 1993Reul et al , 1994.…”
Section: Consequences For Future Drug Treatment Of Depression Currentmentioning
confidence: 95%
“…In the light of the inhibitory effect of MRs on HPA activity which is reflected by studies employing MR antagonists in rats (Spencer et al 1998) and humans (Dodt et al 1993;Young et al 1998) or MR antisense in rats , the observed upregulation of MR capacity seems to be a first step necessary for the inhibition of hypothalamic CRH neurons. This effect on MR is followed by increased GR capacity (Brady et al 1991;Seckl and Fink 1992;Reul et al 1993Reul et al , 1994.…”
Section: Consequences For Future Drug Treatment Of Depression Currentmentioning
confidence: 95%
“…Antidepressants increase mRNA levels of mineralocorticoid receptors (MR) and glucocorticoid receptors (GR), and their hormone binding activities (Kitayama et al, 1988;Seckl and Fink, 1992;Reul et al, 1993Reul et al, , 1994. Also, GR promoter activity is increased by antidepressants, both in vitro (Pepin et al, 1992) and in vivo (Peiffer et al, 1991).…”
Section: Antidepressants and Bdnfmentioning
confidence: 99%
“…Moreover, major depression is known to be frequently accompanied by frontal cortex dysfunction (Soares and Mann 1997;George et al 1999), whereby the frontal cortex is known to exert a regulatory role in HPA system activity (Diorio et al 1993). Findings of blunted hormone responses to stress have been obtained in rats after chronic treatment with various antidepressants (Reul et al 1993(Reul et al , 1994. Thus, since pharmacologically different drugs attenuate HPA system function, this neuroendocrine system was hypothesized to be a common denominator for clinically efficacious antidepressants (Holsboer and Barden 1996).…”
Section: Neuroendocrine Effects Of Rtms: Attenuation Of the Stress-inmentioning
confidence: 99%
“…In this context, HPA system function has been suggested as a common denominator for clinically effective antidepressant treatment strategies (Holsboer and Barden 1996). Indeed, studies of antidepressant action in humans and rats have shown that chronic antidepressant drug treatment is accompanied by an attenuation of HPA system activity (Heuser et al 1996;Reul et al 1993Reul et al , 1994. These findings are further supported by the observation that antidepressants lower the levels of CRH in the cerebrospinal fluid of depressed patients (De Bellis et al 1993).…”
mentioning
confidence: 98%